Perfectionism, Self-Esteem, and the Will to Win Among Adolescent Athletes: The Effects of the Level of Achievements and Gender - Ahmed, Md. Dilsad; Yan Ho, Walter King; Begum, Shaheen; López Sánchez, Guillermo Felipe (Frontiers in Psychology, 2021)
This study examined the relationships between perfectionism, self-esteem, and the will to win and the effects of gender and the level of achievement on these variables. A total of 318 12–19-year-olds (M = 16.10 ± 1.01) completed the Self-Esteem Questionnaire, Will-to-Win Questionnaire, and Perfectionism Inventory. Inter-state-level (ISL) athletes obtained higher scores than inter-district-level (IDL) athletes on the following variables: self-esteem, the will to win, and four of the eight dimensions of perfectionism (i.e., concern over mistakes, the need for approval, organization, and planfulness). Further, male athletes obtained higher self-esteem and perfectionism (i.e., the need for approval and rumination) scores than female athletes. Self-esteem, the will to win, and the dimensions of perfectionism were positively and significantly interrelated. However, one dimension, namely, perceived parental pressure, was unrelated to any factor except striving for excellence. Further, the will to win, concern over mistakes, high standard for others, and planfulness were unrelated to striving for excellence. The results of discriminant analysis revealed that there was no significant difference between ISL and IDL athletes (variance explained = 9.480 %). Lastly, using CFA (path analysis) showed, Model 3 (Perfectionism → Self-esteem → Will to Win) has provided good model fit such as CFI (0.987), TLI (0.876), NFI (0.973), and RMSEA (0.097).